The Effectiveness of Video “6 Steps Hands Wash” to Improve the Capability Hand Washing for Children with Intellectual Disability - Utami, Annisa Putri; Pujaningsih, Pujaningsih (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2021)
This study aims to determine the effectiveness of the "6 - step hand washing" video media to improve the ability to wash hands properly in children with intellectual disability. A student in grade 7th with mild intelectual disability participated in this A1 – B1 – A2 single subject study design. Subject obtained the mean level increased from 30.67 in the phase baseline – 1 (A1) to 54.5 in the intervention phase (B) and 59.33 in the phase baseline – 2 (A2). Changes in the data level experienced an increase in the score, namely from the phase baseline – 1 (A1) to the intervention phase (B) is increased by +18, while in the intervention phase (B) to the phase baseline – 2 (A2) is increased by +2. Data overlap in an analysis of the condition of 0%, which means the video media "hand washing 6 steps" to improve the ability to effectively wash hands properly on the child intellectual disability mild category. There is a need to replicate the study design to increase the external validity and generalization results. The strategies described in the present study may also be useful for special teachers who teach individual with intellectual disability to gain a proper hand washing skills in various context (e.g., home, schools, and public areas).Keywords: video, hand washing, children with intellectual disability